Comparative proteomic analysis reveals the response mechanism of freshwater leech (Whitmania pigra) under heat-stress challenge - Wang, Shuaibing; Zheng, Xiaochuan; Wang, Quan; Wang, Aimin; Wang, Haihua; Fu, Huiyun; Kaunda, Mange; Xiong, Liangwei; Liu, Bo (Comparative biochemistry and physiology. Part D, Genomics & proteomics, 2025)
Temperature is an environmental parameter that remarkably affects the survival and organism health of poikilothermal animal-Whitmania pigra Whitman. Heat stress destroys the physiological homeostasis of intestine tissue. However, no studies on the intestinal mucosa response of leech exposure to heat stress have been reported so far. To identify the biomarker proteins involved in heat stress response, we performed a Tandem mass tag (TMT)-based comparative proteomic analysis on leech's intestine after exposing to 27 °C and 35 °C. The cumulative mortality in the 35 °C heat stress group increased on the third day after stress compared with the control group. Mean-while, intestinal malondialdehyde (MDA) content was significantly up-regulated whereas total antioxidant capacity (T-AOC) was significantly down-regulated. A total of 3935 proteins were identified through proteomic analysis. Heat stress resulted in 144 differential proteins; 75 were up-regulated, and 69 were down-regulated. The differential expression proteins in response to heat stress are mainly involved in calcium-binding proteins, molecular chaperones, cytoskeleton integrity, immune function and inflammation response, DNA damage and repair, ribosomal protein synthesis, stress hormones and neuro-transmitters, tumorigenesis, and apoptosis. Protein-protein network interaction analysis showed that HSP, CD8A, C3, CD63, CD81, MRPL58, MRPL15, HNRNPA1, AMBP, IGHEP1, SERPINC1, CYP3A4, ATP12A, RPS13, CaM, HSP70 binding protein, HSPA6, C4A, ANXA7, ARG1, ARG2, ATP1B, CALCA, HTR1B, and GNGT1 are the critical proteins of leeches resistance to heat stress. Our results systematically provide substantial responsive candidate proteins combating heat stress and enhance our understanding of the intrinsic response mechanisms of thermal sensitivities animal W. pigra facing heat exposure. [Display omitted] •Heat stress destroys the physiological homeostasis of leech intestine.•144 differential proteins were identified under heat-stress challenge.•The Ca2+/CaM/HSP70 pathway involved in regulation to heat stress in leeches.